Synthesis of Cardanol-Based Acetaldehyde Novolac Resin from Cashew Nut Shell Liquid (CNSL) - Surya Dewi Marliyana; Sayekti Wahyuningsih; Nisa Nur Hayati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Polymers are currently in the limelight. Phenolic resin is one of the polymer products obtained from the polymerization process, either from natural or synthetic sources. One of the natural compounds that can be applied to polymers is cardanol. This study aimed to synthesize cardanol-based acetaldehyde novolac resin from Cashew Nut Shell Liquid (CNSL). Isolation of cardanol from CNSL was done by liquid-liquid extraction method with acetone and purified by gravity column chromatography in a mixture of n-hexane and ethyl acetate in a ratio of 9:1. HPLC analysis showed that cardanol compounds had aliphatic chains with different levels of saturation and the yield was 18.48%. The cardanol-acetaldehyde novolac resin was synthesized through a condensation polymerization reaction with a cardanol-acetaldehyde mole ratio (1:0.5), using HCl as a catalyst. FTIR and 1H-NMR analysis were employed to identify the novolac resin structure. The product was a brownish-orange solid with a yield of 12.80 mg (40%) and followed ortho-ortho substitution. Cardanol is one of the natural phenol sources that might be utilized to manufacture novolac resins.